2012
DOI: 10.1016/j.ceramint.2011.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Production of anorthite refractory insulating firebrick from mixtures of clay and recycled paper waste with sawdust addition

Abstract: Production of porous anorthite refractory insulating firebricks from mixtures of two different clays (K244 clay and fireclay), recycled paper processing waste and sawdust addition are investigated. Suitability of alkali-containing-clay, low-alkali fireclay, pore-making paper waste and sawdust in the products was evaluated. Prepared slurry mixtures were shaped, dried and fired. Highly porous anorthite ceramics from the mixtures with up to 30% sawdust addition were successfully produced. Physical properties such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 12 publications
1
30
1
3
Order By: Relevance
“…Porous ceramics have shown promise as functional materials such as filters [1][2][3], catalysts [4], insulators [5][6][7][8][9], sound absorbing materials [10,11], bioceramics [12][13][14], and lightweight refractory materials [15,16]. Furthermore, most porous ceramics are morphologically uniform, and have the same properties in all directions.…”
Section: Introductionmentioning
confidence: 97%
“…Porous ceramics have shown promise as functional materials such as filters [1][2][3], catalysts [4], insulators [5][6][7][8][9], sound absorbing materials [10,11], bioceramics [12][13][14], and lightweight refractory materials [15,16]. Furthermore, most porous ceramics are morphologically uniform, and have the same properties in all directions.…”
Section: Introductionmentioning
confidence: 97%
“…And taking their chemical composition into consideration, a possible effective approach to reuse these wastes is to produce anorthite ceramic. Sutcu et al [32,33] designed a kind of porous anorthite ceramic from paper processing of residues and clay of various sources (i.e. enriched clay, commercial clay and fireclay) at 1200-1400 1C.…”
Section: Introductionmentioning
confidence: 99%
“…13, the predicted values of the universal model did not fit well with the data of this work and Sutcu. 24 It can be concluded that for different pore structures different models should be used to estimate the thermal conductivity based on the open porosity. As shown in Figs.…”
Section: Microstructurementioning
confidence: 99%